Suvorexant (Belsomra® Tablets 10, 15, and 20 mg): Japanese Drug-Use Results Survey - Yuko Asai; Hideki Sano; Makoto Miyazaki; Mika Iwakura; Yoshikazu Maeda; Mitsuyoshi Hara (Adis, Springer Healthcare, 2018)
Abstract Background We report on the results of a Japanese postmarketing drug-use survey of suvorexant (Belsomra®) tablets. Methods A survey with a ≤ 6-month observation period after the start of administration was conducted, targeting insomnia patients who were treated with suvorexant for the first time in Japan. Information on the safety and efficacy of the drug product was collected. The evaluation period was July 21, 2015-August 12, 2017, and the target number of patients was 3428. Results The mean administration period for the safety analysis population of 3248 patients was 113 days. At 6 months after the start of treatment, 48.6% (1577/3248) of the patients had been continually receiving treatment, and 51.4% (1671/3248) of the patients discontinued/dropped out of treatment before 6 months. Among the patients who discontinued/dropped out of the treatment, more than 30% discontinued due to improvement. The mean treatment duration for those who had discontinued treatment for this reason was 62 days. The incidence rate of adverse drug reactions among those in the safety analysis population was 9.7%, and the common adverse drug reactions were somnolence (3.6%), insomnia (1.2%), dizziness (1.1%), and nightmare (0.8%), all of which are described in the product label. No additional noteworthy events were observed. In 2439 patients with a final overall global assessment of sleep judged by physicians, the 'improved' rate was 74.0%. Among 2424 patients who provided a final overall global assessment, the improvement rate was 73.2%, which was comparable with the improvement rate judged by physicians. Regarding clinical effects (based on patient diary data or physician's assessment), reduction in median sleep latency and increase in median total sleep time (reduction from 60 to 50 min and increase from 300 to 360 min compared with baseline, respectively) were observed at 1 week after the start of treatment and onwards, and the effect was maintained after the start of treatment for 6 months. A similar effect was observed irrespective of age groups or reasons for using suvorexant. Conclusion This survey was an exploratory observational study without a control group; the interpretation of results may require the consideration of factors that may have caused bias in the results, such as demographic characteristics and effects of other drugs. However, the results suggest that suvorexant can be a useful drug in daily clinical practice for treating insomnia.